Pharmacokinetics of puerarin in rats, rabbits, and dogs - Jin Xi-Lu; Zhu Xiu-Yuan (Acta Pharmacologica Sinica, 2016)
The puerarin was determined by HPLC with fluorescence detection. The plasma concentration-time course of puerarin in rats and dogs after iv was best fitted to a two-compartment open model, while that in rabbits was best fitted to a three-compartment open model. Species specificity was found among rats, rabbits, and dogs, calculated with compartment model program. The T1/2 beta after iv puerarin 9 mg.kg-1 in rats, rabbits, and dogs were 11, 21, and 67 min, respectively. There were no significant differences in pharmacokinetic parameters after iv 4.5-30 mg.kg-1 to rabbits and dogs.